Bioconjugation of Bacteriophage Pf1 and Extension to Pf1-Based Bionanomaterials - Urquhart, Taylor; Howie, Bradley; Zhang, Lei; Leung, Kam T.; Honek, John F. (Current Nanoscience, 2021)
Background: Filamentous bacteriophages such as M13 are an important class of macromolecular assembly, rich in chemical moieties that can be used to impart modifiable positions at the nanoscale. Objective: To explore the structurally more complex Pf1 bacteriophage with respect to a diverse set of bioconjugation reactions and to prepare novel fluorescently-labelled Pf1-based composite biomembranes for future applications in areas such as nanoporous filtration biofilms and photoconducting nanocomposite materials. Methods: Pf1 was characterized with respect to amine (N-terminal, Gly1 and Lys20), carboxylate (aspartate, glutamate), and aromatic (tyrosine) modification and its extension to the creation of functional biomaterials. Modification with an amine reactive fluorophore was carried out with Pf1. Results: The reaction profiles between M13 and Pf1 differ, with M13 capable of modification at two primary amines on its major coat protein, while Pf1 is capable of a single reaction per coat protein. Subsequent to the production of dye-functionalized Pf1, a biocomposite of wild type and functionalized Pf1 could be fabricated into a bulk material by glutaraldehyde (amine-reactive) crosslinking. These biomaterials were characterized by scanning electron and confocal microscopy, showing a distribution of patches of functionalized Pf1 within the main Pf1 construct. Conclusion: The current study provides a framework for future fabrication of advanced bionanomaterials based on the Pf1 bacteriophage.
Keywords: bioconjugation